2020
DOI: 10.1126/sciadv.aaz8110
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of Kv2.1-VAPA association provides neuroprotection against ischemic stroke in mice by declustering Kv2.1 channels

Abstract: Kv2.1 channels mediate cell death–enabling loss of cytosolic potassium in neurons following plasma membrane insertion at somatodendritic clusters. Overexpression of the carboxyl terminus (CT) of the cognate channel Kv2.2 is neuroprotective by disrupting Kv2.1 surface clusters. Here, we define a seven–amino acid declustering domain within Kv2.2 CT (DP-2) and demonstrate its neuroprotective efficacy in a murine ischemia-reperfusion model. TAT-DP-2, a membrane-permeable derivative, induces Kv2.1 surface c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 50 publications
0
34
0
Order By: Relevance
“…This has been, admittedly, a very difficult problem, to which large amounts of financial resources and numerous careers have been devoted. Our own recent work points to new therapeutic avenues to pursue, targeting Kv2.1-mediated potassium efflux in cell death processes ( Yeh et al, 2017 , 2019 ; Schulien et al, 2020 ). Although ameliorating excitotoxic injury and clinical disability has been very challenging, a better appreciation of critical mechanisms can only improve the potential to succeed in addressing this important unmet medical need.…”
Section: Discussionmentioning
confidence: 99%
“…This has been, admittedly, a very difficult problem, to which large amounts of financial resources and numerous careers have been devoted. Our own recent work points to new therapeutic avenues to pursue, targeting Kv2.1-mediated potassium efflux in cell death processes ( Yeh et al, 2017 , 2019 ; Schulien et al, 2020 ). Although ameliorating excitotoxic injury and clinical disability has been very challenging, a better appreciation of critical mechanisms can only improve the potential to succeed in addressing this important unmet medical need.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, disrupting the phosphorylation-dependent interaction between Kv2.1 and VAP-A ( Kirmiz et al, 2019 ) is neuroprotective and prevents pro-apoptotic K + entry upon ischaemic injury ( Schulien et al, 2020 ). It is particularly interesting that Kv1.1 and Kv2.1 channels were also found to interact with Stx1 ( Fili et al, 2001 ) and SNAP-25 ( MacDonald et al, 2002 ; Leung et al, 2003 ).…”
Section: Er-pm Contact Sites In Neuronsmentioning
confidence: 99%
“…However, side effects associated with broad-spectrum potassium channel blockers, such as tetraethylammonium bromide [ 70 ], have been a crux in the development of a feasible therapy. As a significant advantage in our strategy, many aspects of the molecular events in the Kv2.1 cell death cascade can be targeted for neuroprotection without affecting Kv2.1 basal currents [ 69 , 71 , 72 , 73 ]. We present our two most developed strategies below, as illustrated in Figure 2 C,D.…”
Section: Targeting Kv21 For Neuroprotectionmentioning
confidence: 99%
“…Studies based on this work have demonstrated that overexpression of the C-terminus of the cognate channel, Kv2.2, induces dispersal of these channel clusters [ 82 ], preventing potassium efflux following oxidative injury, and providing neuroprotection in vitro [ 83 ]. In a recent study, we exploited knowledge of this proapoptotic Kv2.1 surface insertion mechanism to validate the targeted-disruption of Kv2.1-VAPA association and cluster dispersal as a neuroprotective strategy [ 73 ].…”
Section: Targeting Kv21 For Neuroprotectionmentioning
confidence: 99%
See 1 more Smart Citation